LIMITATIONS AND CHALLENGES IN THE EARLY DETECTION OF BRAIN TUMORS (Global Conference on Medical and Health Sciences, 2026)
Brain and central nervous system (CNS) cancer is a significant global public health concern due to its high mortality rate, economic impact on individuals and society, low survival rates, and profound effects on patients' quality of life. Brain and central nervous system (CNS) cancers are a significant global health issue. In 2020, there were approximately 308,102 new cases of brain and CNS tumors worldwide. These cancers represent about 1.6% of all new cancer diagnoses globally. Additionally, the disease accounted for 251,329 deaths, making it one of the leading causes of cancer mortality. Survival rates for brain and CNS cancers vary by region and healthcare accessibility, but the prognosis often remains poor due to the aggressive nature of many tumors and challenges in early detection. Neuroimaging plays an increasingly critical role in diagnosing, planning treatment, and assessing outcomes for brain tumors. This review highlights current CT scan methodologies commonly used in brain tumor care, focusing on advanced techniques like contrast-enhanced and non-contrast CT scans for noninvasive tumor characterization and pretreatment assessment. It also explores the value of these imaging methods in evaluating brain conditions, emphasizing the challenges posed by findings such as sclerosis, cysts, and hematomas, which can mimic brain cancer.